СКЛАДОВІ КРИМІНОЛОГІЧНОГО МОНІТОРИНГУ В ДІЯЛЬНОСТІ ОРГАНІВ ПРОКУРАТУРИ - ІЩУК, Олександр Сергійович (SUPREMANCE OF LAW, 2016)
The composition of criminological monitoring of the prosecution is defined. A specific local and regional characteristics of the crime situation is established. It is proved that for effective system of prosecution within the state criminological policy is necessary criminological monitoring.
Keywords: criminological monitoring; prosecution; prevention; counteraction; crime; component